Justifying Secession in Catalonia: Resolving Grievances or a Means to a Better Future? - Elias, Anwen (2021)
This article advances understandings of secessionist strategies by examining how and why secessionist movements make the case for creating a new sovereign state. It draws on new empirical data to examine the ways in which pro-independence parties in Catalonia have justified their calls for the creation of an independent Catalan Republic between 2008 and 2018. The findings challenge the widespread scholarly assumption that secessionist mobilisation is underpinned by grievances—cultural, economic, and political—against the state. We find that arguments for an independent Catalonia rarely include cultural claims. Instead, independence is advocated as a way of resolving political and economic grievances and of creating a better, more democratic, and just Catalan society. Such justifications are highly influenced by the political context in which pro-independence parties try to advance towards secession. These insights advance on extant explanations of secessionist mobilisation by highlighting the distinctive nature of, and the motives for, secessionist claims.